(untitled) (Journal of Pharmaceutical Negative Results, 2014)
Introduction: Monoammonium glycyrrhizinate (MAG) is used as a sweetener and alsoas a flavoring agent to enhance the flavor of dairy products, confectioneries, baked foodsand beverages. It is used in cough drops, cough syrups and cosmetics. It is reported tohave antioxidant, antitussive and antiviral activities. Materials and Methods: The in‑vitroα ‑ amylase inhibitory activity was performed using 3,5‑dinitrosalicylic acid assay. Differentconcentrations (1 μg/ml, 3 μg/ml, 5 μg/ml, 10 μg/ml, 30 μg/ml and 50 μg/ml) of MAGwere analyzed for the α ‑ amylase inhibitory potential. Results: The results of this studyrevealed that MAG lacks α ‑ amylase inhibitory potential. Conclusion: Documentationof pharmacological activities of phytochemicals, which have either positive or negativeoutcome, is required to create a database for phytopharmacological research. The result ofthis study can serve as one of the components of phytochemical research database.